The influence of the drugs “Brovermectin-granulate TM” and “Avesstim TM” on indicators of non-specific resistance of one year-old carp fish infested with monogeneans : ст. - Fedorovych, O. V.; Stybel, V. V.; Gutyj, B. V. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies Lviv, Ukraine, 2022)
The article presents data on the study of the influence of the drugs “Brovermectin-granulate TM” and “Avesstim TM” on indicators of non-specific resistance of one-year-old carp fish infested with monogeneans. For conducting experiments, 14 experimental groups were formed (two groups of each species of fish affected by Dactylogyrus lamellatus, Gyrodactylus hypophthalmichtіdis, Eudiplozoon nipponicum ). The fish of the first experimental group were administered “Brovermectin-granulate TM”, and the second experimental group were administerec a complex of drugs “Brovermectin-granulate TM” and “Avesstim TM”. Fish infected with various ectoparasites (Dactylogyrus lamellatus, Gyrodactylus hypophthalmichtіdis, Eudiplozoon nipponicum ) served as controls. Fish of each group were kept in separate aquariums with a capacity of 40 dm3 with artificial aeration at a temperature of 20–22 °С. Their care and feeding was carried out according to the relevant norms and rations. During the entire period of research, the behavior and clinical condition of the fish were observed. The pre-experimental period of acclimatization of annuals was 7 days. The use of the drug “Brovermectin-granulate TM” to one-year-old white carp, crucian carp and scaly carp affected by monogeneans had a stimulating effect on the resistance of their organism. At the same time, the simultaneous use of the specified drug with the immunomodulator “Avesstim TM” contributed to better activation of the humoral link of non-specific immunity in sick fish. To normalize the organism homeostasis, correct metabolism and activate the humoral link of non-specific immunity during a monogenoid invasion of carp, it is recommended to feed them with a combined feed of the drugs “Brovermectin-granulate TM” and the immunomodulator “Avesstim TM”.
Keywords: carp fish; immunomodulators; dactylogyrus lamellatus; gyrodactylus hypophthalmichtіdis; eudiplozoon nipponicum; риба; карп